(untitled) (ModaPalavra e-periódico, 2018)
Considering the historical, cultural and social importance of the production of bobbin lace in Brazil, this study covers immaterial and material aspects of this heritage, aiming to make a reflection on how the bobbin lace stitches are treated, considering their nomenclatures and textile structures, having as geographic cut two extremes of the country: the southern region and the northeast region. These regions stand out for the artisanal lace production and scientific research on the theme. To reach the goal, 61 stitches were studied and it was observed that only 39.5% of these stitches are known in both regions. It is a qualitative study, based on bibliographical and documental research and technical visit.